Analysing the Impact of Public Awareness on Perceived Ethical Concerns Surrounding AI Startups among Entrepreneurs in Chennai City - Nalini, Dikshita.J (Journal of Informatics Education and Research, 2024)
This study explores the complex relationship between perceived ethical concerns around AI startups among entrepreneurs in Chennai City and public knowledge of these issues. The survey, which involves 120 entrepreneurs, starts with a structured questionnaire designed to gauge public understanding of AI and its ethical implications. The study draws attention to the possible hazards and ethical ramifications of AI technologies, especially in the context of startups. The impact of media on entrepreneurs' ethical concerns is critically examined, with an emphasis on how AI startups are portrayed in different media. The analysis covers the content, tone, and frequency of news stories, reports, and social media conversations around AI startups and moral issues.